Super-plasticizing enhancer for iron ore full-tailing paste filling and preparation method of super-plasticizing enhancer

By using a superplastic reinforcement with a specific ratio, the problems of low mass concentration, low tailings consumption and low early strength in iron ore full tailings sand filling are solved, and the effect of improving the filling quality concentration and early strength is achieved.

CN119683897APending Publication Date: 2025-03-25HUNAN YISHI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802834.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

There are problems in the filling of iron ore full tailings sand, low tailings sand consumption and low early strength of the filling body.

Method used

The superplastic reinforcement consisting of polyether monomers, hydroxyethyl acrylate, polyethylene glycol, ammonium persulfate, ferrous, thiopropionic acid, vitamin C, acrylic acid and triethanolamine, wood pulp, hydrogen peroxide and anhydrous sodium sulfite are used to improve the filling quality of iron ore full tailings sand paste through specific ratios and preparation methods.

Benefits of technology

While ensuring that the fluidity of the filling slurry meets the mine filling requirements, the filling quality concentration is increased by 8-10%, the tailings filling consumption is increased by 30%, and the early strength of the filling body is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a super-plasticizing enhancer for iron ore full-tailing paste filling and a preparation method of the super-plasticizing enhancer, and relates to the technical field of mine filling. The preparation method comprises the following steps: adding a polyether monomer into deionized water, sequentially adding hydroxyethyl acrylate, polyethylene glycol, ammonium persulfate and ferrous iron, and stirring until the materials are dissolved to obtain a material A; adjusting the pH value of wood pulp, adding hydrogen peroxide to react at 65 DEG C, adding anhydrous sodium sulfite to react at 65 DEG C, and cooling to obtain a material D; dropwise adding a solution material B containing mercaptopropionic acid and VC into the material A, stirring and reacting for 4-6 hours, then adding a solution material C containing acrylic acid and triethanolamine, reacting at the temperature of below 60 DEG C, then adding a material D, and mixing. The preparation method of the super-plasticizing enhancer is simple and easy to operate, the filling mass concentration of iron ore full tailings can be increased by 8-10%, the filling consumption of the tailings can be increased by about 30%, the early strength of a filling body can be improved, and the super-plasticizing enhancer belongs to a novel green and environment-friendly material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mine filling, and in particular relates to a superplasticizing intensifier for iron ore whole tailings paste filling and a preparation method thereof, as well as an application of the superplasticizing intensifier in iron ore whole tailings paste filling materials. Background Art

[0002] With the continuous deepening of mineral resource mining, the disposal and utilization of iron ore tailings has become an important issue in the industry. Tailings not only occupy a large amount of land, but also may pollute the environment and groundwater. Therefore, by reforming the industrial structure and using tailings for filling mining, it is possible to not only reduce the harm of tailings to the environment, but also improve the comprehensive utilization rate of mineral resources and realize efficient and green mining of ferrous metal mines.

[0003] The content of -400 mesh of iron ore tailings is 43.2%, the content of -200 to +400 mesh is 18.2%, and the content of +200 mesh is 38.6%. The tailings particle size is fine, and the water requirement for preparing the filling slurry is high. The mass concentration of the filling slurry is low, generally around 50%~57%. The tailings consumption is small, and the early strength of the filling body is low.

[0004] The solution to the above-mentioned iron ore tailings filling defects is to add new materials, increase the iron ore tailings filling mass concentration, increase the tailings filling consumption, and improve the early strength of the filling body. Therefore, how to increase the iron ore tailings filling mass concentration, increase the tailings filling consumption, and improve the early strength of the filling body has become the research focus of existing technicians. Summary of the invention

[0005] The main purpose of the present invention is to provide a filling superplasticizing strengthener for iron ore whole tailings paste. The preparation method is simple and easy to operate, and can effectively improve the problems of low mass concentration of iron ore whole tailings filling, low tailings consumption, low early strength of the filling body, etc., and it belongs to a green and environmentally friendly new material.

[0006] In order to achieve the purpose of the present invention, the present invention provides a superplasticizing strengthener for filling iron ore tailings paste, which is composed of the following raw materials in parts by weight: 40-65 parts of material A, 15-25 parts of material B, 5-15 parts of material C and 15-30 parts of material D; Wherein, the components of the material A are polyether monomers, hydroxyethyl acrylate, polyethylene glycol, ammonium persulfate and ferrous iron; The components of the B material are mercaptopropionic acid and vitamin C; The components of the C material are acrylic acid and triethanolamine; The components of the D material are wood pulp, hydrogen peroxide and anhydrous sodium sulfite.

[0007] Furthermore, the preparation method of the D material is: add dilute alkali solution to an appropriate amount of wood pulp to adjust the pH value to 8-9, then add hydrogen peroxide, react at 55-70°C for 3-5h, then add anhydrous sodium sulfite, react at 55-70°C for 2-4h, and naturally cool to room temperature to obtain the D material.

[0008] Furthermore, the amount of hydrogen peroxide added is 5-8% of the mass of the wood pulp; The amount of anhydrous sodium sulfite added is 10-15% of the mass of the wood pulp.

[0009] Furthermore, the components of the material A are as follows by weight: 60-75 parts of polyether monomers, 10-20 parts of hydroxyethyl acrylate, 5-10 parts of polyethylene glycol, 1.0-1.5 parts of ammonium persulfate and 3-6 parts of ferrous iron.

[0010] Furthermore, the polyether monomer is any one of vinyl polyoxyethylene ether, methyl allyl polyether or isopentanol polyoxyethylene ether.

[0011] Furthermore, the mass ratio of mercaptopropionic acid to VC in the material B is (0.2-0.4):1.

[0012] Furthermore, the mass ratio of acrylic acid to triethanolamine in the C material is (0.3-0.5):1.

[0013] The present invention also provides a method for preparing a superplasticizing strengthener for filling iron ore tailings paste, which specifically comprises the following steps: S1. Material A: Add an appropriate amount of deionized water to the reactor and start stirring, add polyether monomers, and then add hydroxyethyl acrylate, polyethylene glycol, ammonium persulfate, and ferrous iron in sequence to fully dissolve them; S2. Prepare material B: Add an appropriate amount of deionized water to the container bottle, add mercaptopropionic acid and VC, and fully dissolve them; S3. Preparation of material C: Add an appropriate amount of deionized water to a container bottle, add acrylic acid, triethanolamine and deionized water to fully dissolve; S4. Add the above material B dropwise to material A, stir and react for 3-5 hours, then add material C and stir and react for 1-2 hours, then add material D and mix well to obtain a superplasticizer.

[0014] Furthermore, in step S4, the initial dropping temperature of material B is not more than 20°C, the dropping time is 120-180min, the dropping end temperature is not more than 30°C, and the stirring reaction temperature is not more than 30°C; In the step S4, the initial dropping temperature of the C material does not exceed 30°C, the dropping time is 100-160 min, the dropping end temperature does not exceed 60°C, and the stirring reaction temperature does not exceed 60°C.

[0015] The superplasticizer prepared by the preparation method of the superplasticizer for iron ore whole tailings paste filling provided above is used in the iron ore whole tailings paste filling, and is added at 0.2-0.7% of the total mass of the iron ore whole tailings paste filling slurry.

[0016] The present invention has achieved the following beneficial effects: 1. The superplasticizing enhancer of the present invention adopts a unique physical and chemical process at room temperature and pressure, and is prepared by a composite of environmentally friendly biomass and safe and environmentally friendly surfactants. It is a safe, non-toxic, harmless, environmentally friendly high-plasticizing enhancing functional solvent. While ensuring that the fluidity of the filling slurry meets the requirements of mine filling, it can increase the original iron ore filling mass concentration by 8-10%, increase the tailings filling consumption by about 30%, and improve the early strength of the filling body. It is a new green and environmentally friendly material.

[0017] 2. The present invention adopts wood pulp, hydrogen peroxide and anhydrous sodium sulfite in an appropriate amount to prepare material D, so that it interacts with material A, material B and material C in the superplasticizer, reduces the adsorption of water by the whole iron ore tailings in the slurry, and then reduces its water demand, increases the filling mass concentration of the whole iron ore tailings, improves the fluidity of the slurry, and makes the superplasticizer have better bonding, hydrophobic and good dispersibility, which is convenient for the material raw materials in the filling slurry to bond tightly; at the same time, a lubricating film is formed on the surface of the filling paste, which can flow with low resistance in pipelines, tunnels and other scenes, and has better slurry and easy transportability.

[0018] 3. The superplasticizing strengthener of the present invention can give full play to the hydration and hardening bonding performance of the glue particles and the iron ore tailings particles, thereby greatly improving the early and late strength of the filling body. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The superplasticizing enhancer for filling iron ore tailings paste of the present invention and its preparation method and application are described below in conjunction with specific embodiments.

[0021] The preparation method of the superplasticizing strengthener for iron ore used for filling the iron ore tailings paste of this embodiment is: S1. Configuration of material A: 1.3kg of deionized water was added to the reactor and stirring was started. 6.0kg of prenol polyoxyethylene ether was added, followed by 2.0kg of hydroxyethyl acrylate, 1.0kg of polyethylene glycol, 100g of ammonium persulfate and 600g of ferrous iron to fully dissolve; S2. Prepare material B: add an appropriate amount of deionized water to the container bottle, add 1.5kg of mercaptopropionic acid and 5kg of VC (vitamin C), and fully dissolve them; S3. Preparation of material C: Add an appropriate amount of deionized water to a container bottle, add 2kg of acrylic acid and 5kg of triethanolamine to fully dissolve; S4. Preparation of material D: 15% dilute sulfuric acid was added to 5.0kg of wood pulp (wood powder selected from Zhu Kun new materials, model 60-80 mesh) to adjust the pH value to 8.5, then 400g of hydrogen peroxide was added, reacted at 65 ° C for 4h, then 500g of anhydrous sodium sulfite was added, reacted at 65 ° C for 3h, and then cooled to room temperature to obtain material D; S5. At a temperature below 20°C, place 4.0kg of material A in a reactor, then drop 1.5kg of material B into material A while stirring, and control the dropping time within 125±5min to ensure that the temperature does not exceed 30°C at the end of the dropping. After the dropping is completed, stir the reaction at a rate of 1200rpm for 5h, and the reaction temperature does not exceed 30°C; then drop 1.5kg of material C into material A while stirring, and control the dropping time within 155±5min. After the dropping is completed, stir and mix at a rate of 1200rpm for 1h, and the temperature does not exceed 60°C, ensuring that the temperature does not exceed 60°C at the end of the dropping; finally, add 3.0kg of material D to material A and mix evenly to obtain a superplasticizer.

[0022] The preparation method of the superplasticizing strengthener for iron ore used for filling the iron ore tailings paste of this embodiment is: S1. Configuration of material A: 1.55kg of deionized water was added to the reactor and stirring was started. 7.5kg of vinyl polyoxyethylene ether was added, followed by 1.0kg of hydroxyethyl acrylate, 500g of polyethylene glycol, 150g of ammonium persulfate and 300g of ferrous iron to fully dissolve; S2. Prepare material B: add an appropriate amount of deionized water to the container bottle, add 1.5kg of mercaptopropionic acid and 5kg of VC (vitamin C), and fully dissolve them; S3. Preparation of material C: Add an appropriate amount of deionized water to a container bottle, add 2kg of acrylic acid and 5kg of triethanolamine to fully dissolve; S4. Preparation of material D: Add 15% dilute sulfuric acid to 5kg of wood pulp to adjust the pH to 8.5, then add 250g of hydrogen peroxide, react at 65°C for 4h, then add 750g of anhydrous sodium sulfite, react at 65°C for 3h, and naturally cool to room temperature to obtain material D; S5. At a temperature below 20°C, place 5.2kg of material A in a reactor, then drop 2.0kg of material B into material A while stirring, and control the dropping time within 175±5min to ensure that the temperature does not exceed 30°C at the end of the dropping. After the dropping is completed, stir the reaction at a rate of 1200rpm for 3h, and the reaction temperature does not exceed 30°C; then drop 1.0kg of material C into material A while stirring, and control the dropping time within 105±5min. After the dropping is completed, stir and mix at a rate of 1200rpm for 2h, and the temperature does not exceed 60°C, ensuring that the temperature does not exceed 60°C at the end of the dropping; finally, add 1.8kg of material D to material A and mix evenly to obtain a superplasticizer.

[0023] The preparation method of the superplasticizing strengthener for iron ore used for filling the iron ore tailings paste of this embodiment is: S1. Configuration of material A: 1.3kg of deionized water was added to the reactor and stirring was started. 7.0kg of methyl allyl polyether was added, followed by 1.5kg of hydroxyethyl acrylate, 600g of polyethylene glycol, 120g of ammonium persulfate and 480g of ferrous iron to fully dissolve; S2. Prepare material B: add an appropriate amount of deionized water to the container bottle, add 1.5kg of mercaptopropionic acid and 5kg of VC (vitamin C), and fully dissolve them; S3. Preparation of material C: Add an appropriate amount of deionized water to a container bottle, add 2kg of acrylic acid and 5kg of triethanolamine to fully dissolve; S4. Preparation of material D: Add 15% dilute sulfuric acid to 5kg of wood pulp to adjust the pH to 8.5, then add 310g of hydrogen peroxide, react at 65°C for 4h, then add 620g of anhydrous sodium sulfite, react at 65°C for 3h, and naturally cool to room temperature to obtain material D; S5. At a temperature below 20°C, place 6.5kg of material A in a reactor, then drop 1.5kg of material B into material A while stirring, and control the dropping time within 150±5min to ensure that the temperature does not exceed 30°C at the end of the dropping. After the dropping is completed, stir the reaction at a rate of 1200rpm for 4h, and the reaction temperature does not exceed 30°C; then drop 0.5kg of material C into material A while stirring, and control the dropping time within 130±5min. After the dropping is completed, stir and mix at a rate of 1200rpm for 2h, and the temperature does not exceed 60°C, ensuring that the temperature does not exceed 60°C at the end of the dropping; finally, add 1.5kg of material D to material A and mix evenly to obtain a superplasticizer.

[0024] Comparative Example 1 The preparation method of the superplasticizing agent for filling the iron ore tailings paste in Comparative Example 1 and the raw materials and proportions used are the same as those in Example 3, and specific reference is made to Example 3. The difference is that no D material is added in Comparative Example 1, and the other components and process parameters are the same.

[0025] Comparative Example 2 The preparation method of the superplasticizing strengthener for filling the iron ore tailings paste in this comparative example 2 and the raw materials and proportions used are the same as those in Example 3, and specific reference is made to Example 3. The difference is that no D material is added in this comparative example 2, that is, the specific preparation method is: S1. Configuration of material A: After adding 1.08kg of deionized water to the reactor and stirring, add 5.8kg of vinyl polyoxyethylene ether, then add 1.6kg of hydroxyethyl acrylate, 800g of polyethylene glycol, 120g of ammonium persulfate, 600g of ferrous iron, and stir until completely dissolved; S2. Prepare material B: add an appropriate amount of deionized water to a container bottle, add 3kg of mercaptopropionic acid and 5kg of VC (vitamin C), and fully dissolve; S3. Prepare material C: Add an appropriate amount of deionized water to a container bottle, add 2kg of acrylic acid and 5kg of triethanolamine, and fully dissolve; S4. Place 7.2kg of material A in a reactor at a temperature below 20°C, then drop 2.2kg of material B into material A while stirring, and control the dropping time within 180±5min to ensure that the temperature does not exceed 30°C at the end of the dropping. After the dropping is completed, stir the reaction at a rate of 1200rpm for 6h, and the reaction temperature does not exceed 30°C; then drop 1.6kg of material C into material A while stirring, and control the dropping time within 130±5min. After the dropping is completed, stir and mix at a rate of 1200rpm for 2h, and the temperature does not exceed 60°C, and ensure that the temperature does not exceed 60°C at the end of the dropping, and the desired superplasticizer is obtained.

[0026] Comparative Example 3 The preparation method of the superplasticizing strengthener for filling the iron ore tailings paste in this comparative example 3 and the raw materials and proportions used are the same as those in Example 3, and specific reference is made to Example 3. The difference is that the preparation method of material D in this comparative example 3 is: add 15% dilute sulfuric acid to 5kg of wood pulp to adjust the pH value to 8.5, then add 310g of hydrogen peroxide and 620g of anhydrous sodium sulfite, react at 65°C for 7h, and naturally cool to room temperature to obtain material D.

[0027] Comparative Example 4 The preparation method of the superplasticizing fortifier for filling the iron ore tailings paste in this comparative example 4 and the raw materials and proportions used are the same as those in Example 3, and specific reference is made to Example 3. The difference is that the material D in this comparative example 4 is wood pulp whose pH value is adjusted to 8.5 using 15% dilute sulfuric acid, and no hydrogen peroxide and anhydrous sodium sulfite are added.

[0028] Comparative Example 5 The preparation method of the superplasticizing strengthener for filling the iron ore tailings paste in this comparative example 5 and the raw materials and proportions used are the same as those in Example 3, and specific reference is made to Example 3. The difference is that the preparation method of the D material in this comparative example 5 is: add 15% dilute sulfuric acid to 5kg of wood pulp to adjust the pH value to 8.5, then add 310g of hydrogen peroxide, react at 65°C for 4h, and naturally cool to room temperature to obtain the D material.

[0029] Comparative Example 6 The preparation method of the superplasticizing strengthener for filling the iron ore tailings paste in this comparative example 6 and the raw materials and proportions used are the same as those in Example 3, and specific reference is made to Example 3. The difference is that the preparation method of the D material in this comparative example 6 is: add 15% dilute sulfuric acid to 5kg of wood pulp to adjust the pH value to 8.5, then add 620g of anhydrous sodium sulfite, react at 65°C for 3h, and naturally cool to room temperature to obtain the D material.

[0030] The superplasticizer prepared in the above Examples 1-3 and Comparative Examples 1-3 was added to the iron ore tailings paste filling slurry, and prepared according to the method of "Test Method for Cement Mortar Strength (ISO)" (GB / T17671-2021). After preparation, various properties were tested according to the corresponding standards. The test results are shown in Table 1 below. Among them, the iron ore tailings paste filling slurry is composed of iron ore tailings, the superplasticizing enhancer of the present invention, a cementitious material and water; the filling concentration refers to the mass percentage of the filling components (i.e., solid components) in the filling slurry, including the iron ore tailings, the binder and the superplasticizing enhancer; the cementitious material is the reference cement (P.O42.5) used by the building materials department to test the properties of the admixture, and the dosage is calculated based on the total solid mass; the particle size of the iron ore tailings is -400 mesh, the content is 43.2%, the content of -200 to +400 mesh is 18.2%, and the content of +200 mesh is 38.6%; the superplasticizing enhancer (i.e., the reagent referred to in Table 1) is prepared in this embodiment and the comparative example, and the dosage (i.e., the reagent dosage) is calculated based on the total solid mass; the water is tap water. Please refer to the preparation parameters and test items in Table 1 below.

[0031] Table 1 Performance test data of iron ore tailings paste filling slurry

[0032] It can be seen from the test data in Table 1 above that after the superplasticizer is added to the iron ore full tailings paste filling slurry, while ensuring that the fluidity of the filling slurry meets the mine filling requirements, the amount of filling cementitious material is reduced, the filling mass concentration is increased by 10%, and the tailings consumption is increased by 33%, solving the problem of low iron ore full tailings filling mass concentration and low tailings consumption.

[0033] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0034] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A superplasticizing intensifier for filling iron ore tailings paste, characterized in that: The invention is composed of the following raw materials in parts by weight: 40-65 parts of material A, 15-25 parts of material B, 5-15 parts of material C and 15-30 parts of material D; Wherein, the components of the material A are polyether monomers, hydroxyethyl acrylate, polyethylene glycol, ammonium persulfate and ferrous iron; The components of the B material are mercaptopropionic acid and vitamin C; The components of the C material are acrylic acid and triethanolamine; The components of the D material are wood pulp, hydrogen peroxide and anhydrous sodium sulfite.

2. The superplasticizing strengthener for filling iron ore full tailings paste according to claim 1, characterized in that: The preparation method of the D material is as follows: add dilute alkali solution to an appropriate amount of wood pulp to adjust the pH value to 8-9, then add hydrogen peroxide, react at 55-70° C. for 3-5 hours, then add anhydrous sodium sulfite, react at 55-70° C. for 2-4 hours, and naturally cool to room temperature to obtain the D material.

3. The superplasticizing strengthener for filling iron ore full tailings paste according to claim 2, characterized in that, The amount of hydrogen peroxide added is 5-8% of the mass of the wood pulp; The amount of anhydrous sodium sulfite added is 10-15% of the mass of the wood pulp.

4. The superplasticizing strengthener for filling iron ore tailings paste according to claim 1, characterized in that: The components of the material A are as follows by weight: 60-75 parts of polyether monomer, 10-20 parts of hydroxyethyl acrylate, 5-10 parts of polyethylene glycol, 1.0-1.5 parts of ammonium persulfate and 3-6 parts of ferrous iron.

5. The superplasticizing strengthener for filling iron ore full tailings paste according to claim 4, characterized in that: The polyether monomer is any one of vinyl polyoxyethylene ether, methyl allyl polyether or isopentanol polyoxyethylene ether.

6. The superplasticizing strengthener for filling iron ore tailings paste according to claim 1, characterized in that: The mass ratio of mercaptopropionic acid to VC in the material B is (0.2-0.4):

1.

7. The superplasticizing strengthener for filling iron ore tailings paste according to claim 1, characterized in that: The mass ratio of acrylic acid to triethanolamine in the C material is (0.3-0.5):

1.

8. A method for preparing a superplasticizing strengthener for filling iron ore tailings paste as claimed in any one of claims 1 to 7, characterized in that: The specific steps include: S1. Material A: Add an appropriate amount of deionized water to the reactor and start stirring, add polyether monomers, and then add hydroxyethyl acrylate, polyethylene glycol, ammonium persulfate, and ferrous iron in sequence to fully dissolve them; S2. Prepare material B: Add an appropriate amount of deionized water to the container bottle, add mercaptopropionic acid and VC, and fully dissolve them; S3. Preparation of material C: Add an appropriate amount of deionized water to a container bottle, add acrylic acid, triethanolamine and deionized water to fully dissolve; S4. Add the above material B dropwise to material A, stir and react for 3-5 hours, then add material C and stir and react for 1-2 hours, then add material D and mix well to obtain a superplasticizer.

9. The method for preparing a superplasticizing strengthening agent for filling iron ore full tailings paste according to claim 8, characterized in that: In the step S4, the initial dropping temperature of the material B is not more than 20°C, the dropping time is 120-180min, the dropping end temperature is not more than 30°C, and the stirring reaction temperature is not more than 30°C; In the step S4, the initial dropping temperature of the C material does not exceed 30°C, the dropping time is 100-160 min, the dropping end temperature does not exceed 60°C, and the stirring reaction temperature does not exceed 60°C.

10. Use of a superplasticizer prepared by the preparation method according to claim 8 or 9 in filling of iron ore tailings paste, characterized in that: Add 0.2-0.7% of the total mass of the iron ore tailings paste filling slurry.